Socialne, čustvene in medkulturne kompetence učiteljev - Vršnik Perše, Tina (Sodobna pedagogika, 2020)
The purpose of the present study was to examine the social, emotional and intercultural competencies of teachers in more detail and to determine the predictive value of these competencies for teachers' satisfaction with their work. The paper focuses on the results of a pilot study of the project HAND in HAND (Kozina et al., 2017), which was conducted among teachers in Slovenia (N = 97, gender: F = 89.7%, age: M = 44.05 years, SD = 9.55). The validity of the internal structure of each questionnaire was checked by Exploratory Structural Equation Modeling (ESEM) and multiple regression analysis was used to verify the predictive value of the variables. In a sample of Slovenian teachers, we investigated the relationship between social and emotional competencies according to CASEL (2015) (self-awareness, self-management, social awareness, relationship skills) and intercultural competencies in relation to teachers' satisfaction with their work. The overall model, with all included predictors of emotional, social, and intercultural competencies, explains 34% of the variance in teachers' job satisfaction, with the strongest predictor being relational skills. This justifies the importance of developing these competencies throughout the professional development of teachers.
Keywords: čustvene kompetence; medkulturne kompetene; profesionalni razvoj; socialne kompetence; strokovna usposobljenost; učitelji; zadovoljstvo